Alu-mediated 100-kb deletion in the primate genome: The loss of the agouti signaling protein gene in the lesser apes - Nakayama, Kazuhiro; Ishida, Takafumi

(untitled) (Genome Research, 2006)
Agouti signaling protein (ASIP) is an endogenous antagonist of melanocortin receptors that controls a wide range of physiological functions. Its central role in regulation of the melanocortin system implied that ASIP has been relevant to the evolution of various physiological traits in primates. In this study, we have tried to determine DNA sequences of the ASIP gene (ASIP) of various simian species to find molecular evolutionary aspects of ASIP. Unexpectedly, we found that the whole coding region of ASIP was missing only from the gibbon genome; gibbons constitute a large group of hominoid species in Southeast Asia. Our analyses revealed that unequal homologous recombination mediated by two AluSx elements erased a ∼100-kb region including ASIP from the gibbon genome. The data provide new evidence for the significant roles of Alu elements in the dynamic evolution of the primate genome.